The Role of “Digital Warrior Teachers” in Optimizing the Utilization of Interactive Flat Panel through the Technology Ambassador Community - Anijar Hapni Siregar; Maya Novita Sari (FKIP - Universitas Riau, 2026)
This study aims to analyze the strategic role of